REGIONAL FEATURES AGE OF MOTHER AND ANTHROPOMETRIC CHARACTERISTICS OF NEWBORN CHILDREN REPUBLIC OF CRIMEA - Балакчина, Анна Игоревна; Каладзе, Николай Николаевич; Лагунова, Наталья Владимировна (Mother and Baby in Kuzbass, 2022)
The study aims – study of regional characteristics of the age of mothers living in the Republic of Crimea and the main anthropometric indicators of newborn children of the Republic of Crimea (body weight, body length) depending on the age of the woman.Material and methods. The study was conducted on the basis of GBUZ RK «Simferopol Clinical Maternity Hospital No. 1». A retrospective analysis of medical documentation was carried out: 1300 Childbirth histories (form N 096/y) of women living in the Republic of Crimea.Results. A study was made of the age of mothers at the birth of a child living in the Republic of Crimea. It was found that the largest number of births occurred in the age interval of 26-30 years (35.69 %), approximately the same number of births occurred in the intervals of 31-35 (26.08 %) and 21-25 years (23.31 %). The minimum number of births falls on the intervals of age younger than 20 years (3.92 %) and older than 40 years (1 %). The average age of mothers was within 28.91 ± 5.05 years. The minimum age is 16 years, the maximum is 47 years. The average number of pregnancies was 2.22 ± 1.32, childbirth – 1.76 ± 0.86. In the age period up to 20 years, women had the first and second births, in the remaining age intervals there are births from the first to the sixth. The difference between the average age of mothers at the birth of the first child and the second child is 3.76 years. Between subsequent births, it decreases and is between the second and third – 1.9 years, the third and fourth – 1.67 years, the fourth and fifth – 0.6 years towards the fourth child, and only between the fifth and sixth increases, and is 4,47 years old.Regional features of the age of mothers living in the Republic of Crimea were revealed. The region fits into the general picture of the Russian Federation of increasing the age of mothers at childbirth. The average age of mothers at the birth of the first child was 26.47 ± 4.54 years, the second – 30.23 ± 4.51 years, the third – 32.13 ± 3.99 years, the fourth – 33.80 ± 4.50 years, the fifth – 33.20 ± 4.13 years old, the sixth – 37.67 ± 8.62 years old. Depending on the age of the mother, an assessment was made of the main anthropometric indicators of newborns in the Republic of Crimea (body weight and length).Conclusion. The results obtained made it possible to identify regional features of the age of mothers living in the Republic of Crimea and the main anthropometric indicators of newborns of the Republic of Crimea (body weight, body length) depending on the age of the woman.
Keywords: mother's age; number of births; newborn children; anthropometric characteristics; body weight; body length